Given:
[tex]\dfrac{1+\sin \theta}{\cos \theta}+\dfrac{\cos \theta}{1+\sin \theta}=2\sec \theta [/tex]
To prove:
The given statement.
Proof:
We have,
[tex]\dfrac{1+\sin \theta}{\cos \theta}+\dfrac{\cos \theta}{1+\sin \theta}=2\sec \theta[/tex]
Taking LHS, we get
[tex]\text{LHS}=\dfrac{1+\sin \theta}{\cos \theta}+\dfrac{\cos \theta}{1+\sin \theta}[/tex]
Taking LCM, we get
[tex]\text{LHS}=\dfrac{(1+\sin \theta)^2+cos^2\theta }{\cos \theta(1+\sin \theta)}[/tex]
[tex]\text{LHS}=\dfrac{(1)^2+2\sin \theta +\sin^2 \theta+cos^2\theta }{\cos \theta(1+\sin \theta)}[/tex] [tex][\because (a+b)^2=a^2+2ab+b^2][/tex]
[tex]\text{LHS}=\dfrac{1+2\sin \theta +1}{\cos \theta(1+\sin \theta)}[/tex] [tex][\because \sin^2 \theta+cos^2\theta =1][/tex]
[tex]\text{LHS}=\dfrac{2+2\sin \theta}{\cos \theta(1+\sin \theta)}[/tex]
[tex]\text{LHS}=\dfrac{2(1+\sin \theta)}{\cos \theta(1+\sin \theta)}[/tex]
[tex]\text{LHS}=\dfrac{2}{\cos \theta}[/tex]
[tex]\text{LHS}=2\sec \theta[/tex] [tex][\because \sec\theta=\dfrac{1}{\cos \theta}][/tex]
[tex]\text{LHS}=\text{RHS}[/tex]
Hence proved.